Entrelaçamento de vozes em Vidas secas de Graciliano Ramos - Sandrini, Elizabete Gerlânia Caron (2012)
With the corpus of research the novel Vidas Secas (Barren Lives) of Graciliano Ramos, this paper aims to undertake a critical-analytical reflection that seeks to show how different voices and oppose social dialogue in this tissue polyphonic work which consists basically of a monologue interior. The object of study, the character Fabiano, his thoughts have reproduced authentically, which is guided by the narrator in free indirect discourse to give voice to this being almost "speechless". Taking up this in view, through an analysis that weaves the teachings of the Russian theorist Mikhail Bakhtin about the polyphonic novel and the French duo Gilles Deleuze and Félix Guattari on the theory of manifolds, relations dialogical between Fabiano and other social voices of the novel will be presented.